Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Say you have the polynomial $$ x^4 + 2 + x^{-4} $$

Looking at it, you see you can do $$\begin{align*} x^4 + 1 + 1 + x^{-4} & =x^2( x^2 + x^{-2} ) + x^{-2}( x^2 + x^{-2} )\\ &= \left( x^2 + x^{-2} \right)^2. \end{align*}$$ Another one is $$\begin{align*} x^2 + \frac{1}{2} + \frac{1}{16x^2} &= x^2 + \frac{1}{4} + \frac{1}{4} + \frac{1}{16x^2} \\ &=x^2\left( 1 + \frac{1}{4x^2} \right) + \frac{1}{4}\left( 1 + \frac{1}{4x^2} \right)\\ &=\left( x^2 + \frac{1}{4}\right) \left( 1 + \frac{1}{4x^2} \right)\\ (x^2) \left( 1 + \frac{1}{4x^2} \right)^2. \end{align*}$$

So the question is, I've been doing this by "inspection" - are there any techniques for recognizing when this type of factorization is possible or how to do more easily?

share|improve this question
1  
You have $A(x) + B + C(x)$, set $a = \sqrt{A(x)}, b = \sqrt{C(x)}$ and check if $2ab = B$. (So that $(a+b)^2 = a^2 + 2ab + b^2$.) In your fist example $a=x^2, b=x^{-2}$, in the second $a=x, b=\frac{1}{4x}$. –  Eelvex Mar 22 '11 at 14:37
    
math.stackexchange.com/questions/21232/… –  anonymous Mar 22 '11 at 15:02
add comment

1 Answer

up vote 3 down vote accepted

For trinomials:

  • If you have $(p(x))^2 + K + (q(x))^2$, then check to see if $K = \pm 2p(x)q(x)$. if so, then $(p(x))^2 + K + (q(x))^2 = (p(x)\pm q(x))^2$.

    • In your first example, you have $$x^4 + 2 + x^{-4} = (x^2)^2 + 2 + (x^{-2})^2.$$ Taking $p(x) = x^2$, $q(x) = x^{-2}$, we have $2p(x)q(x) = 2$, which is precisely the middle term, so $x^2+2+x^{-4} = (x^2 + x^{-2})^2$.
    • In your second example, you have $$x^2 + \frac{1}{2} + \frac{1}{16x^2} = (x)^2 + \frac{1}{2} + \left(\frac{1}{4x}\right)^2.$$ Taking $p(x) = x$ and $q(x) = \frac{1}{4x}$, you have $2p(x)q(x) = \frac{2x}{4x} = \frac{1}{2}$, again exactly the middle term, so you get $$x^2 + \frac{1}{2} + \frac{1}{16x^2} = \left(x + \frac{1}{4x}\right)^2.$$
  • More generally, if you have $(p(x))^2 + Kp(x) + L$, then see if you can find two expressions, $s(x)$ and $t(x)$, which when multiplied give $L$ and when added give $K$, $s(x)t(x) = L$, $s(x)+t(x) = K$. Then $(p(x))^2 + Kp(x) +L = (p(x)+s(t))(p(x)+t(x))$.

    • For example, $$2x^4 + (\sqrt{2}-1)x^2 + x.$$ You may notice that the leading term is $(\sqrt{2}x^2)^2$, and that you have a "middle term" of $\sqrt{2}x^2$. So rewriting a bit you get $$(\sqrt{2}x^2)^2 + (\sqrt{2}x^2)1 + (x-x^2).$$ This suggests looking for $s(x)$ and $t(x)$ with $s(x)+t(x) = 1$ and $s(x)t(x)=x-x^2 = x(1-x)$. This in turn quickly suggests $s(x) = x$ and $t(x)=1-x$, which gives $$2x^4 + (\sqrt{2}-1)x^2 + x = \left(\sqrt{2}x^2 + x\right)\left(\sqrt{2}x^2 + (1-x)\right).$$

But generally, there is some substantial amount of "inspect and notice" going on. The more of these you do, the more you will notice patterns and be able to "notice" the things that one needs to notice.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.